Peningkatan Kualitas Ekonomi Masyarakat Melalui Pelatihan Kewirausahaan Budidaya Jamur Organik Yang Ramah Lingkungan Di Pekanbaru - Sehani Sehani; Herlinda Herlinda; Ainun Mardiah; Ratna Dewi (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
This community service activity aims to provide training on how to produce organic mushrooms and increase public insight about the prospects and business opportunities of oyster mushrooms. In the implementation of this community service, there are several methods or forms of activities that will be carried out and suitable for solving various problems in service activities, including lecture and practice methods. In this community service, target audiences who are considered strategic to be involved in this community service activity are mushroom farmers and people who are interested in cultivating mushrooms. This mushroom business has good prospects because there is public awareness of the benefits and nutritional value contained in mushrooms so that the interest in the community to consume mushrooms increases and affects the demand for mushrooms. If this agribusiness can be continued and developed properly, it will have an effect on increasing the income of the people of Pekanbaru City